Managerial economics : theory, applications, and cases - Mansfield, Edwin. (W. W. Norton, 1999)
This book is divided into six parts: Introduction; Demand and forecasting; Production and cost; market structure, strategic behavior, and Pricing; Risk analysis and capital budgeting; and Government-Business relations and the global economy.